Will there be Malaysia spring? A comparative assessment on social movements - Nidzam Sulaiman; Kartini Aboo Talib @ Khalid (Penerbit Universiti Kebangsaan Malaysia, 2017)
Arab Spring was within the premonition because the Middle-east had been a place of contestation since the birth of Judaism and Christianity. Arab Spring caught the attention of the world when the mass movements trumpeting the voice calling for equal rights led to the downfall of dictators in several countries. These countries are labelled as Muslim countries which include Tunisia, Egypt, Libya, Syria, Yemen, Bahrain, Morocco, Jordan and Oman. Some of them experienced less volatile changes. The question is does Malaysia that labelled as a Muslim country will experience such surged by the masses like the Arab spring or will there be Malaysia spring? This paper examines this possibility through several factors such as socio-economic position, the role of the state, history and social structure, and the media in influencing the political awareness of the masses. Although neighbouring countries such as Indonesia, the Philippines and Thailand appear to have similar uprising, the results of mass movement in those countries have brought about different results. The concept of hegemony and political awareness are explained in this study. The findings indicate that there is a slim possibility of Malaysia spring due to the aforementioned factors. This study is descriptive and interpretive in nature and only the secondary data are used for the conceptual analysis.